Common frame of reference and existing EC contract law: [symposium held in December 2007 [...] at the University of Münster, Germany] - Schulze, Reiner (Sellier European Law Publ., 2008)
The academic draft of the CFR and the EC contract law / Reiner Schulze -- Comparative law and common frame of references / Konstantinos D. Kerameus -- "A Better Coherence of EU Private Law" and multilingualism / Gianmaria Ajani -- Contract law or law of obligations? / Hans Schulte-Nölke -- Contracts between consumer protection and trade usages / Giuditta Cordero Moss -- Pre-contractual duties-from the acquis to the common frame of reference / Christian Twigg-Flesner -- Non-discrimination / Stefan Leible -- The right of withdrawal, the acquis principles and the draft common frame of reference / Evelyne Terryn -- Non-negotiated terms / Thomas Pfeiffer -- The remedies for non-performance in the system of the acquis group / Fryderyk Zoll -- The damages rules in the acquis communautaire, in the acquis principles and in the DCFR / Ulrich Magnus -- The common frame of reference (CFR) of European insurance contract law / Helmut Heiss -- DCFR and property law: the need for consistency and coherence / Sjef van Erp -- Cadre commun de réference et droit international privé / Paul Legarde -- Europäisches Vertragsrecht - Österreichische Haltung / Georg Kathrein -- Connection between the CFR and a possible horizontal instrument of consumer law / Judit Fazekas
Keywords: Konferenzschrift -- 2007 -- Münster; Gemeinschaftlicher Besitzstand; Vertragsrecht; Europäische Union